THE RELATIONSHIP BETWEEN THE ABILITY TO PERFORM ACTIVITIES OF DAILY LIVING WITH RISK FOR FALLS AMONG OLDER ADULTS IN TRESNA WERDHA SOCIAL SERVICE BANYUWANGI - Luthfi Fadlilatun Nisa; Latifa Aini; Kholid Rosyidi (Journal of Nursing Science Update (JNSU), 2019)
Increasing number of older adults makes them less productive which causes a decline in their independence to perform the activities of daily living. One of the physical problems that causes morbidity and mortality among older adults is fall. The purpose of this research was to analyse the relationship between the ability to perform activities of daily living and risk for falls among older adults in Tresna Werdha Banyuwangi. This research applied non experimental correlational design and cross sectional approach. The objects of research were 71 older adults. The sample was taken using total sampling which was comprised of 65 older adults that fulfilled inclusion criteria. Katz Index, Morse Fall Scale (MFS), and observation sheet were used to collect the data. Those data analysed using chi square test. The result of the older adults ability in performing activities in daily living showed that categorised as mild and the mildest dependent 17 older adults  (26,1%)  with low and high risk of falls were. Test resulted in p value 0,002 (p <α = 0,05) which suggested that there was a relationship between the ability to perform activities of daily living and risk for falls. Medical staff are expected to provide nursing care in addressing risk for falls, providing ambulatory aid  to help maintaining balance while walking, teaching the patients what to do when they fall, so they don’t suffer serious injury, by monitoring the movement, and by holding a routine physical program.